Who should set the Standards? : Analysing Censored Arabic Content on Facebook during the Palestine-Israel Conflict - Magdy, Walid; Mubarak, Hamdy; Salminen, Joni (ACM, 2025)
Nascent research on human-computer interaction concerns itself with fairness of content moderation systems. Designing globally applicable content moderation systems requires considering historical, cultural, and socio-technical factors. Inspired by this line of work, we investigate Arab users’ perception of Facebook’s moderation practices. We collect a set of 448 deleted Arabic posts, and we ask Arab annotators to evaluate these posts based on (a) Facebook Community Standards (FBCS) and (b) their personal opinion. Each post was judged by 10 annotators to account for subjectivity. Our analysis shows a clear gap between the Arabs’ understanding of the FBCS and how Facebook implements these standards. The study highlights a need for discussion on the moderation guidelines on social media platforms about who decides the moderation guidelines, how these guidelines are interpreted, and how well they represent the views of marginalised user communities.
Keywords: Censorship; Content Moderation; Free Speech; Palestine Israel Conflict; social media; Facebook; fi=Markkinointi|en=Marketing|